A TRIBUTE TO THEODORE ROSZAK. THE MAKING OF A COUNTERCULTURE - Ştefan BORBÉLY (Studia Universitatis Babeş-Bolyai. Philologia, 2019)
A Tribute to Theodore Roszak. The Making of a Counterculture. The American professor Theodore Roszak (1933 – 2011) is generally credited with the invention of the term “counterculture”, although his seminal book from 1969, The Making of a Counter Culture spells the two words separately. To us, today it seems to be the work of a rather cautious, but pioneering sociologist, who acknowledges indeed the legitimacy of the student revolts of the Sixties but at the same time tries to distance himself from their heat with the cool objectivity of the academic observer.